Evaluation of dilute-and-shoot and solid-phase extraction methods for the determination of S-metolachlor and metolachlor-OA in runoff water samples by liquid chromatography tandem mass spectrometry. Issue 39 (28th September 2017) - Arias, Jean Lucas de Oliveira; Schneider, Antunielle; Batista-Andrade, Jahir Antonio; Vieira, Augusto Alves; Gehrke, Vinicios Rafael; Camargo, Edinalvo Rabaioli; Caldas, Sergiane Souza; Primel, Ednei Gilberto
Abstract : Two fast methods employing dilute-and-shoot and SPE were evaluated for fast determination of S -metolachlor and Metolachlor-OA in runoff water samples. Abstract : In this study, two fast methods, i.e., the dilute-and-shoot one and the solid-phase extraction (SPE) procedure, were evaluated for the determination of S -metolachlor and metolachlor-OA in runoff water samples by liquid chromatography tandem mass spectrometry (LC-MS/MS). The limits of quantification of both analytes were 2 μg L −1 and 0.02 μg L −1, by dilute-and-shoot and SPE, respectively. Good accuracy (86–114%) and precision (≤20%) were found. Besides, these methods were statistically similar. Thus, firstly, dilute-and-shoot is a promising alternative to analyzing samples with high levels of both analytes. Secondly, samples with low levels of both analytes can be submitted to SPE. Both methods were successfully employed, since they enabled the determination of S -metolachlor and metolachlor-OA in runoff water samples at concentrations between 0.082 and 267 μg L −1 .